Pengaruh Kepemimpinan Kepala Sekolah dan Kinerja Guru terhadap Prestasi Peserta Didik di MA Nurul Furqon Cibinong Bogor - Qomarudin Qomarudin; Nanat Fatah Natsir; Mohamad Jaenudin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
The problem of this research is about improving the quality of education output which is reflected in the achievements of the students, is the expectation of all schools starting from the principal and also teachers who teach as well as both parents, but in reality there are still many students who actually have achievements but not yet seen or even do not know the achievements in themselves, so they can and have the achievements as expected. The problem in this study is limited around the principal's leadership and teacher performance, as well as the achievement of the students themselves. The research method used in this study is a quantitative method. This research is correlational because this study seeks to investigate the effect of school principal leadership and teacher performance on student achievement. The results showed that (1) there was a positive influence between the principals' leadership variables on the achievement of students obtained the value of the analysis of 2.464 so that the positive results were concluded, the level of strong influence. (2) there is a positive influence between teacher performance on student achievement obtained value of 2.868 so that concluded positive results, the level of influence is strong. (3) simultaneously the leadership of the school principal and the performance of the teacher have a very significant effect on the achievement of students in MA NurulFurqon, Cibinong District, Bogor Regency.